THE IMPLEMENTATION OF CRITICAL READING IN THE CLASSROOM - Rita Risnawati (Journal of English Education Program (JEEP), 2019)
This paper aims to know the implementation of critical reading in the classroom. Critical reading is a skill highly necessitated in both academic and everyday lives. A critical reader is able to detect bias, prejudice, misleading opinion, and illogical conclusions, in a text. As a reading skill which involves critical thinking competence, critical reading can be defined as the process of understanding, questioning, and evaluating a text, which is carried out actively and consciously, in order to well assess the accuracy and validity of a writer’s ideas. As a skill, critical reading could be developed through learning and practices. To know their problems, the researcher proposes a research question: How is critical reading implemented in the classroom? What are the students’ perception toward the implementation of critical reading in the classroom? To get the data the researcher used two instruments Observation and close- ended Questionnaires. The writer takes one English teacher and students of Eleventh grade in Senior High School consisted 28 of students. To interpret the data, the writer uses qualitative design particularly case study design. The result in this study it was concluded that the process of the implementation of critical reading consists of three stages such as pre-reading stage, while- reading stage and post reading stage. The process of the implementation of critical reading worked well, the learning process was effective, the students are more motivated to learn and critical reading process can improve students' reading ability and the student look like enjoy learning using critical reading.